Comparative transcriptome analyses of different orthosiphon aristatus tissues reveal differentially expressed genes associated with flavonoid biosynthesis - Qiaoxue Wang; Huan Long; Shumeng Liu; Xixi Xu; Qin Zhang; Shanyong Yi (Scientific Reports)
Abstract Orthosiphon aristatus (O. aristatus) has been used as a popular traditional folk medicine for the treatment of kidney disease. Recent studies have shown that O. aristatus root contains more flavonoids and has higher antioxidant capacity compared to its medicinal parts. However, there is limited knowledge on the mechanisms behind the synthetic biology of flavonoid in all tissues of O. aristatus. Here, we performed high-performance liquid chromatography (HPLC) analysis and comparative transcriptome analyses of flavonoids in all tissues. The content of 4 major flavonoids is significantly higher in roots and leaves compared to stems in O. aristatus. Out of a total of 138,294 Unigenes, the KEGG pathway analysis identified 66 Unigenes encoding 8 key metabolic enzymes involved in the biosynthetic pathway of flavonoid compounds. Additionally, 5,154 on average DEGs involved in flavonoid biosynthesis could be categorised into 58 transcription factor (TF) families. Among the identified DEGs, a total of 5,897 were common to all tissues, with 212 DEGs strongly associated with flavonoid accumulation in root. Several of these key enzyme genes were further validated by quantitative real-time polymerase chain reaction (qRT-PCR). Our research provides novel insights into flavonoids synthetic biology, and highlights O. aristatus root may serve as a valuable resource for medicinal use.